2006
DOI: 10.1002/mrd.20645
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of embryonic stem cell‐like cells from in vitro‐produced buffalo (Bubalus bubalis) embryos

Abstract: This study was carried out to isolate and characterize buffalo embryonic stem (ES) cell-like cells from in vitro-produced embryos. Inner cell mass (ICM) cells were isolated either mechanically or by enzymatic digestion from 120 blastocysts whereas 28 morulae were used for the isolation of blastomeres mechanically. The ICM cells/ blastomeres were cultured on mitomycin-C-treated feeder layer. Primary cell colony formation was higher (P < 0.05) for hatched blastocysts (73.1%, 30/41) than that for early/expanded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 41 publications
9
59
2
Order By: Relevance
“…In a present study, the morphology of BuES-like cells on BEF was observed to be similar to our previous study [16], and closely resembled porcine [39] and cat [30] ES cells. However, the colony morphology was found to vary on heterologous feeder layers where they appeared compact, thinner and flatter but with clear margins on GEF feeder layers and appeared to carry loose cells with increased intercellular spacing and showed lack of clear margins on SEF feeder layers.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In a present study, the morphology of BuES-like cells on BEF was observed to be similar to our previous study [16], and closely resembled porcine [39] and cat [30] ES cells. However, the colony morphology was found to vary on heterologous feeder layers where they appeared compact, thinner and flatter but with clear margins on GEF feeder layers and appeared to carry loose cells with increased intercellular spacing and showed lack of clear margins on SEF feeder layers.…”
Section: Discussionsupporting
confidence: 89%
“…As stated earlier in various reports, homologous feeder cell layers supported self renewal and maintained pluripotent characteristics of human and monkey ES cells, with characteristics similar to those of ES cells cultured on mouse fetal fibroblast (MEF) [9,15]. Recently, buffalo embryonic stem cell-like cells have been generated on buffalo fetal fibroblasts [16,17]; although the buffalo ES (BuES) cell-like cells grew on homologous feeder cell layers but cell colonies did not maintain an undifferentiated state over a long period of time. Whether the absence of specific factors or other unknown attributes of buffalo embryonic fibroblast (BEF) affected the self-renewal of BuES-like cells is not known.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations